Analisis Prinsip Prinsip Pembelajaran Ips - Septian, Amar; Nazar, Muhammad; Heri, Kusai; Paturahman, Maman; Sudrajat, Yayan (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2024)
This research aims to process and analyze information related to (1) social studies learning and (2) social studies learning principles. This research takes the form of a literature study. The data collection method used is the documentation method for library study procedures, namely topic selection, information exploration, determining research focus, collecting data sources, reading data sources, making research notes, processing research notes, and preparing reports. The data source is bibliographic or comes from various literature, including books, journals, newspapers, personal documents, and so on. The instrument in library research is the researcher himself. The results of social science research integrate social sciences such as geography, economics, history and sociology. The research results show that (1) Social Studies has a close relationship with Social Sciences. The relationship between Social Studies and Social Sciences is that Social Sciences is based on Social Studies. However, learning at school in Social Studies is different from Social Sciences. The location of these differences lies in the level of thinking of students at the level of education. (2) The principles of social Studies learning refer to learning integration, learning interaction, continuity and change in learning material, contextual learning material.